PERAN USER-GENERATED CONTENT DI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN IMPULSIF PELANGGAN STARBUCKS COFFEE DI BANDARA SAM RATULANGI MANADO - Rosary Patricia Mekel; Yoan Purnamasari Makapuase Bahalau; Zerah Elisa Derek (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the influence of User-Generated Content (UGC) on social media on impulse buying decisions of Starbucks Coffee customers at Sam Ratulangi Airport, Manado. Airports as captive markets present a unique context where transient consumers with available waiting time are exposed to social media content that can trigger spontaneous purchasing behavior. The study employed a quantitative approach with a survey method involving 150 respondents selected through purposive sampling. The research instrument was a Likert scale 1–5 questionnaire comprising 27 statement items. Data were analyzed through validity testing (Pearson), reliability testing (Cronbach's Alpha), classical assumption tests, and simple linear regression using SPSS 26. Results indicate that UGC has a positive and significant effect on impulse buying decisions (β = 0.713; t = 9.141; p < 0.001), with a coefficient of determination (R²) of 0.510, meaning UGC explains 51.0% of the variance in impulse buying decisions. Content credibility was the dominant predictor (mean = 4.21). These findings underscore the critical importance of UGC-based digital content management in F&B marketing strategies in travel retail environments, particularly in Eastern Indonesia where empirical studies remain scarce. Keywords : User-Generated Content, Impulse Buying, Social Media, Travel Retail, Starbucks